Electrical Properties of Composite Polyaniline/Superconducting Ceramic: Polyaniline/Neodymium-Barium-Copper Oxide - Fernandes, J.P.; Duarte, G.W.; Caldart, C.; De Mello, J.M.M.; Dal Magro, J.; Riella, H.G.; Fiori, M.A. (Asian Journal of Chemistry, 2014)
Polyaniline (PANI) is one of the most attractive conductor polymers due to its high conductivity, chemical stability and easy polymerization. Polyaniline can be applied to actuators, super-capacitors, electromagnetic devices and especially gas sensors. The neodymium-barium-copper ceramic, produced by oxide compounds (NBCo), is a special ceramic material that can be used as superconductive material at relatively high temperatures, depending on the treatment that it is submitted during its synthesis. Therefore, the union of these two materials creates a versatile composite. This study evaluated the electrical properties of NBCo composites in a polymeric matrix of polyaniline at high temperatures. The parameters evaluated were the particle size, percentage of NBCo in the polymeric matrix and the composite temperature. The results showed that the conductivity is dependent on the particle size, percentage of NBCo and temperature. An increase in the temperature, in the particle size of NBCo compound and a decrease of NBCo percentage in the polyaniline matrix contribute to increase the electrical conductivity of the composite. The curve of current versus electric potential showed a non-Ohmic behavoiur for all compositions and testing conditions.